Experimental Investigation of Armour (Armox-Aramid-UHMWPE) - Viliš, Jindřich; Vítek, Roman; Zouhar, Jan; Stejskal, Michal; Neumann, Vlastimil (Manufacturing Technology Journal, 2023)
In this study, the ballistic resistance of multi-layered composite armour is experimentally investigated. The composition of this armour consisted of armour steel Armox 500T, para-aramid fabric Twaron CT 747 and ultra-high molecular weight polyethylene Endumax Shield XF33. To compare the ballistic resistance, the ballistic resistance of the armour with the perforated steel Armox 500T was tested. The rifle cartridges 7.62 x 51 mm FMJ NATO M80 were used to test this resistance. The aim of this experiment was to compare the ballistic resistance of unperforated and perforated steel Armox 500T. As part of the experimental part, the chemical composition and microhardness of the steel Armox 500T was verified. The hardness of the composite materials was also measured for optimal armor configuration. After the projectile impact, the damage mechanism of the steel Armox 500T and the composite materials were investigated by using optical and electron microscopy. It was proved that the ballistic resistance of the perforated steel depends on the used pattern. Based on the performed experiments, the steel Armox with pattern A effectively reduced the weight of the testing configuration and absorbed all the kinetic energy of the projectile 7.62 mm FMJ M80.
Keywords: Ballistic resistance; Armour protection; Perforated sheet; Composite; Aramid